Answer:
y - 1 =
(x - 2)
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
Here m =
and (a, b) = (2, 1), thus
y - 1 =
(x - 2) ← equation of line
Answer:
c) 0.0156
Step-by-step explanation:
The general term a[n] of a geometric sequence is given in terms of the first term a[1] and common ratio r as ...
a[n] = a[1]r^(n-1)
The given sequence has an initial term of a[1]=8 and a common ratio of 4/8=1/2. Then the general term is ...
a[n] = 8(1/2)^(n-1)
The 10th term is then ...
a[10] = 8(1/2)^(10-1) = 8(1/2)^9 = 8/512
a[10] = 0.015625 ≈ 0.0156
Answer:
y = kx
Step-by-step explanation:
In proportional relationships, the value of one variable increases as the other increases or decreases as the other decreases. It is denoted mathematically as y ∝ x where x and y are the variables. It follows that
y = kx where k is the proportionality constant.
So in the relationship where x represents the number of adults, and y represents the number of students,
y ∝ x and y = kx
y = kx is the required equation
Answer:
<u>200</u>
Step-by-step explanation:
pi · radius · height
3.14 · 8 · 25 = 200
extra : i used symbolab.com :)
The answer is D
Explanation 4 ones is 4